Beyond Training: How Professional Development Transforms K-12 Teachers’ Job Satisfaction, Networking, and Social Mobility - Egure, Dominic; Curry, Katherine (International Journal of Multicultural Education, 2025)
Since 2010, technological advancements have revolutionized teachers’ professional development (PD), increasing its accessibility and flexibility. This shift reflects a growing emphasis on lifelong, personalized learning that addresses educators’ unique contexts and challenges. This qualitative case study explores Nigerian teachers’ perceptions of a PD program designed to support their professional growth. Findings reveal key themes, including enhanced job satisfaction, expanded social networking, strengthened human capital, and opportunities for upward social mobility. The study also identifies barriers to PD participation, offering insights into how educators engage professional learning. These results underscore the transformative potential of PD in empowering teachers and advancing educational equity.